2020
DOI: 10.1002/tox.23030
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of ferruginol on isoprenaline hydrochloride‐induced myocardial infarction in rats

Abstract: Cardiovascular‐related diseases continue to be a leading cause of death globally. Among ischemic‐induced cardiac diseases, myocardial infarction (MI) is reported to be of an alarming value. Despite numerous improvements in the medical intrusions, still this armamentarium fails to be effective in managing the illness without setbacks. Ferruginol (FGL) is a major polyphenols and terpenoids with numerous pharmacological activities including antioxidant and anti‐inflammatory. Following, this work was aimed to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The COL‐SF group showed higher TBARS concentration when compared to healthy. MI may reduce the activity of antioxidant enzymes, 35,36 explaining the low activity of GPx in all infarcted groups. Zhang and colegahes 35 reported that antioxidant enzymatic activity was induced by increasing ROS concentration.…”
Section: Discussionmentioning
confidence: 93%
“…The COL‐SF group showed higher TBARS concentration when compared to healthy. MI may reduce the activity of antioxidant enzymes, 35,36 explaining the low activity of GPx in all infarcted groups. Zhang and colegahes 35 reported that antioxidant enzymatic activity was induced by increasing ROS concentration.…”
Section: Discussionmentioning
confidence: 93%
“…Nicotinamide nucleotide transhydrogenase (NNT, Spd:O = 1.571) is a nuclear gene encoded protein located in the mitochondrial inner membrane, which catalyzes mitochondrial transmembrane hydride transfer between NAD(H) and NAD(P)+ to generate NAD(P)H. It has been demonstrated that the NAD+/NADH ratios affect the activity of the sirtuins family, which are potential mediators of the beneficial effects of calorie restriction and mediating lifespan, and an age-dependent loss of gene expression of NNT which linked to mitochondrial dysfunction ( Olgun, 2009 ). Moreover, NNT increases NADPH level, which is important for antioxidant systems, biosynthesis, aging, and apoptosis ( Zhang et al, 2021 ). NNT overexpression can be used as management strategies to decrease the ratio of NADH/NAD+ and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage and mitochondrial dysfunction are associated with increased LPO and reduced endogenous antioxidant enzymes in the myocardial tissue. 41 , 42 The enzymatic antioxidant myocardial system works in a coordination manner to maintain the cellular redox balances. During the ISO treatment, a disturbance occurred in the redox balance in the myocardial.…”
Section: Discussionmentioning
confidence: 99%
“…LPO is a crucial pathogenic process in the condition of cardiac injury and the effect of ISO on LPO in the myocardial tissue of rodents is well established. 41 , 42 The peroxidative injury is exerted through the quinone formation (intermediates of ISO), which reacts with the molecular oxygen to generate the ROS and induces the membrane LPO. 41 In this experimental protocol, gossypin considerably suppressed the ISO mediated TBARS (LPO marker) in myocardial tissue, suggesting a potent antioxidant effect to protect the myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation